Production of Fragrance Tag (Paper-Based Air Fresheners) from Agarwood Powder Waste (Aquilaria malaccensis) - Yuniarti, Reni; Wardani Putri, Elfira; Sida Mubin, Abror; Achmad, Feerzet (Eksergi, 2025)
Agarwood is a non-timber forest product known for its distinctive fragrance. Its processing generates powder waste that is often undervalued and underutilized, despite containing aromatic compounds with potential for value-added products such as fragrance tags. This study aimed to determine the optimal composition of agarwood powder and waste paper, assess the effects of NaOH treatment on product characteristics, and evaluate economic feasibility. The process involved preparing agarwood and HVS paper waste, treating with or without NaOH, producing pulp at ratios of 75:25, 50:50, and 25:75 (% w/w), and adding essential oil. Results showed that NaOH treatment significantly improved physical and sensory properties such as color brightness, grammage, and tensile strength but reduced thickness, absorbency, and aroma retention. Material ratio also influenced performance: 25:75 (% w/w) with NaOH yielded the best color and tensile strength, while 75:25 without NaOH showed the highest thickness, absorbency, and aroma stability up to day 5. Economic analysis indicated feasibility, with a break-even point of 181 units, a return cost ratio (RCR) of 1.44, and a payback period of 2.27 months.